إدارة الصراع في شمال غرب سوريا وتأثيره على العلاقات التركية الروسية - غراف, عبدالرزاق (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
يعد ملف إدارة الصراع في شمال غرب سوريا أحد أكثر الملفات تأثيرا على العلاقات التركية الروسية، وستحاول هذه الدراسة التطرق لمعضلة إدارة الصراع في شمال غرب سوريا من منظور الطرفين التركي الروسي، وذلك من خلال إبراز مواقف الطرفين تجاه تطورات الاحداث في هذه المنطقة وإمكانية تحولها لصدام مباشر بينهما، حاولت الدراسة الاجابة على الاشكالية الآتية: ما مدى التوافق والاختلاف بين تركيا وروسيا في ملف إدارة الصراع في شمال غرب سوريا، وما مدى إمكانية تطور حدة الصراع بما يؤدي لصدام مباشر بينهما؟، وقد خلصت الدراسة الى أن الصراع في شمال غرب سوريا يمتلك كبير التأثير في العلاقات التركية الروسية، هذه الأخيرة التي ورغم تطورها في السنوات الأخيرة إلا أن فشل الطرفين في ادارة الملف بما يحفظ مصالح الطرفين وبخاصة الطرف التركي يهدد هذا التطور، ما يجعل كل من تركيا وروسيا أمام حتمية إيجاد مخارج ولو مؤقتة لملف إدارة الصراع في شمال غرب سوريا وهو الحاصل لغاية اللحظة. الكلمات المفتاحية: إدارة الصراع، شمال غرب سوريا، تركيا، روسيا، العلاقات التركية الروسية Abstract: The management of the conflict in northwest Syria is one of the most influential issues on Turkish-Russian relations. The present study attempts to address the dilemma of that conflict from the perspective of the Turkish and Russian parties, by highlighting the positions of the two sides towards the development of events in the region and the extent of its transformation into a direct clash between them. The study tried to answer the following problem: What is the degree of compatibility and difference between Turkey and Russia in the conflict management in northwestern Syria, and the level to which the intensity of the conflict can develop, leading to a direct clash between them?, The study concluded that the conflict in northwest Syria has a great impact on Turkish-Russian relationships, the latter of which, despite its development in recent years, the failure of the two parties to manage the conflict in a manner that preserves the interests of both parties, especially the Turkish side, threatens this development, which makes both Turkey and Russia In front of the inevitability of finding exits, even if temporary, to the conflict management in northwest Syria, which is the case until now. Keywords: Conflict management, northwest Syria, Turkey, Russia, Turkish-Russian relationships.